Peace Education and Economic Empowerment for Terrorism Inmates Within the Roots of Radicalism: Lessons from Lamongan - Rayhan Aulia Prakoso; Muhammad Maulana Masudi; Moh. Anas Kholish (Pustaka Peradaban, 2025)
This study examines the nexus between peace education and economic empowerment in the deradicalization of terrorism convicts, with a case study of the Yayasan Lingkar Perdamaian (YLP) in Lamongan, Indonesia—an institution founded by former terrorism perpetrators who have transformed into peace agents. Radicalism, rooted in ideological rigidity and socio-economic disparities, requires a multidimensional approach that goes beyond ideological deconstruction by integrating humanistic and welfare-oriented strategies. This research aims to analyze how YLP combines peace education and economic empowerment to dismantle residual extremism while reconstructing the social identity of former convicts as legitimate members of society. Using a qualitative case study method, data were collected through participatory observation, in-depth interviews, and document analysis. The findings reveal that experiential peace education, spiritual narratives, and transformative dialogue, when coupled with economic initiatives through social entrepreneurship and community networks, create restorative spaces that facilitate identity recovery and social reintegration. This study recommends the mainstreaming of cultural-humanistic approaches in national deradicalization policies and emphasizes the critical role of former perpetrators as key actors in peacebuilding. The novelty of this research lies in highlighting the synergy between ideological reconciliation and economic empowerment as a grassroots paradigm for sustainable deradicalization. Penelitian ini mengkaji keterkaitan antara pendidikan perdamaian dan pemberdayaan ekonomi dalam proses deradikalisasi narapidana terorisme melalui studi kasus Yayasan Lingkar Perdamaian (YLP) di Lamongan, Indonesia—sebuah lembaga yang didirikan oleh mantan pelaku terorisme yang telah bertransformasi menjadi agen perdamaian. Radikalisme yang berakar pada rigiditas ideologis dan kesenjangan sosial-ekonomi memerlukan pendekatan multidimensional yang tidak hanya berfokus pada dekonstruksi ideologi, tetapi juga mengintegrasikan strategi humanistik dan kesejahteraan. Penelitian ini bertujuan menganalisis bagaimana YLP menggabungkan pendidikan perdamaian dan pemberdayaan ekonomi untuk melemahkan sisa-sisa ekstremisme sekaligus merekonstruksi identitas sosial mantan narapidana sebagai anggota masyarakat yang sah. Dengan menggunakan metode studi kasus kualitatif, data dikumpulkan melalui observasi partisipatif, wawancara mendalam, dan analisis dokumen. Temuan menunjukkan bahwa pendidikan perdamaian berbasis pengalaman, narasi spiritual, dan dialog transformatif, ketika dipadukan dengan inisiatif ekonomi melalui kewirausahaan sosial dan jejaring komunitas, mampu menciptakan ruang restoratif yang mendorong pemulihan identitas dan reintegrasi sosial. Penelitian ini merekomendasikan pengarusutamaan pendekatan kultural-humanistik dalam kebijakan deradikalisasi nasional serta menekankan pentingnya keterlibatan mantan pelaku sebagai aktor utama dalam pembangunan perdamaian. Kebaruan penelitian ini terletak pada penegasan sinergi antara rekonsiliasi ideologis dan pemberdayaan ekonomi sebagai paradigma akar rumput untuk deradikalisasi yang berkelanjutan